Hispanic Review, A Quarterly Journal Devoted to Research in the Hispanic Languages & Literatures, Published by the Department of Romance Languages, University of Pennsylvania, Philadelphia, vols. 40-42, 1972-1974. - Valderrama Andrade, Carlos (Thesavrvs, 2023)
Reseña de revistas.